Repeat sprint ability - Turner, A. N.; Stewart, P. F. (Strength and Conditioning Journal, 2013)
Sprint speed is related to the ability to deplete large amounts of high-energy phosphates at a fast rate. To sprint repeatedly, the aerobic system must resynthesize polymerase chain reaction, remove accumulated intracellular inorganic phosphate, and oxidize lactate during rest periods. Whether this can be appreciably improved via a high vo2max remains controversial. However, it is likely improved via anaerobic qualities such as strength, power, and speed, along with the athlete's velocity at onset of blood lactate accumulation. When reporting repeat sprint ability test results, total or mean time should be used.